Simultaneous anterior shoulder dislocation and Salter Harris type 2 fracture in Senegalese wrestling match - Camara, Ibrahima S.; Diallo, Hawa L.; Conde, Mamady S.; Hachim, Mohamed (International Journal of Research in Orthopaedics, 2025)
Anterior shoulder dislocation with proximal humerus fracture in children is rare. We report the case of a 16 years old boy with anterior shoulder dislocation and proximal humerus fracture separation Salter Harris type 2. A 16 years old boy, right-handed, was involved in a wrestling accident. He was received for delayed left shoulder traumatism associated with a filling of the deltopectoral groove, an emptiness of the glenoid cavity without axillary nerve impairment. Anterior shoulder dislocation with Proximal humerus fracture-separation type 2 Salter Harris was made. The dislocation was reduced through external manoeuver. A Kirschner wire fixation was done for both the fracture and the glenohumeral joint. At the last follow up, the shoulder was painless, stable, with satisfactory motion. The consolidation was obtained. Anterior shoulder dislocation with proximal humerus fracture separation Salter Harris type 2 is rare. Good management restores shoulder motion and function.